Effect of Ni additions and hot deformation on precipitation behavior and hardness in AleSieMg aged alloys - Castro Carmona, Javier Servando (2020)
Additions of 1e2 Ni (wt. %) and hot deformation on the microstructure and hardness of A356 aged alloy were studied. The results show that the addition of this element generates the formation of Ni31Si12 and NiFe phases with high thermal stability. In addition, the presence of Ni into the Al matrix and precipitates of the second phase affect the precipitation kinetics, transformation sequence, growth rate, and slow loss of hardness in the system after reaching the maximum values. For example, the Ni additions contribute to generating the coexistence of b" precipitate and GP-I zones. Of all the strengthening mechanisms present, hardening by precipitation is the most influential in the hardness